Compositional influence of local and long-range polarity in the frustrated pyrochlore system Bi2−xRExTi2O7 (RE = Y3+, Ho3+). Issue 37 (6th June 2022) - Bailey, Owen; Husremovic, Samra; Murphy, Madison; Ross, Jason; Gong, Joyce; Olds, Daniel; Laurita, Geneva
Abstract : Cation off-centering is crystallography frustrated in the pyrochlore but exhibits local ordering. Abstract : Structural distortions such as cation off-centering are frustrated in the pyrochlore structure due to the triangular arrangement of cations on the pyrochlore lattice. This geometric constraint inhibits a transition from a paraelectric to a ferroelectric phase in the majority of pyrochlore oxide materials. Few pyrochlore materials can overcome this frustration and exhibit polar crystal structures, and unraveling the origin of such leads to the understanding of polarity in complex materials. Herein we hypothesize that frustration on the pyrochlore lattice can be relieved through A-site doping with rare earth cations that do not possess stereochemically active lone pairs. To assess if frustration is relieved, we have analyzed cation off-centering in various Bi2− x RE x Ti2 O7 (RE = Y, Ho) pyrochlores through neutron and X-ray total scattering. Motivated by known distortions from the pyrochlore literature, we present our findings that most samples show local distortions similar to the β-cristobalite structure. We additionally comment on the complexity of factors that play a role in the structural behavior, including cation size, bond valence, electronic structure, and magnetoelectric interactions. We posit that the addition of magnetic cations on the pyrochlore lattice may play a role in an extension of the real-space correlation length of electric dipoles in the Bi-Ho series, and offer considerations for driving long-range polarity on the pyrochlore lattice.